3D-Image analysis of the impact of toothpaste abrasivity on the progression of simulated non-carious cervical lesions. (June 2018) - Sabrah, Alaa H.; Turssi, Cecilia P.; Lippert, Frank; Eckert, George J.; Kelly, Adam B.; Hara, Anderson T.
Abstract: Objectives: To investigate the effect of toothpaste abrasive level on the progression of non-carious cervical lesions (NCCLs) using 3D-image subtraction. Methods: Upper first premolars were allocated into seven groups (n = 16) of toothpaste/abrasive slurries: A-Zeodent113/5%, B-Zeodent124/10%, C-Zeodent103/15%, D-Sensodyne Pronamel, E-Crest Cavity-Protection, F-Crest Pro-Health-Whitening, and G-Deionized water (DIW). Teeth were mounted on acrylic blocks, and their root surfaces covered with acrylic resin, except for 2-mm near the cemento-enamel junction that was exposed to toothbrushing. Specimens were brushed with the slurries for 5000-, 15, 000-, 35, 000- and 65, 000-strokes. Impressions were taken at baseline and after each brushing time, and then scanned by a 3D optical profilometer. Dentine volume loss was calculated by image subtraction software and subjected to mixed-model ANOVA and multiple comparison tests (α = 0.05). Results: No significant differences among slurries were observed at 5000 and 15, 000. At 35, 000, F showed higher loss than all other groups except C, which did not differ from the others. At 65, 000, F (4.19 ± 3.29 mm 3 ) showed the highest loss, followed by C (2.33 ± 1.47 mm 3 ), which differed from all the other groups except B (1.85 ± 0.91 mm 3 ). Groups B, A (1.35 ± 0.65 mm 3 ), D (1.17 ± 0.48 mm 3 ), E (1.40 ± 0.68 mm 3 ) and G (1.12 ± 0.73 mm 3 ) did not differ from each other. Groups F and C showed significant increase of volume loss starting at 35, 000, while B, A, D and E only at 65, 000; no increase loss was observed for G. Conclusions: 3D-image subtraction was able to quantify and differentiate tooth loss, but only at advanced stages. The progression of NCCLs was more evident and faster for highly abrasive slurries. Clinical significance: Upon root dentin exposure, brushing with lower abrasive dentifrices is advisable to reduce the risk for NCCLs development.